2007
DOI: 10.1113/expphysiol.2006.035378
|View full text |Cite
|
Sign up to set email alerts
|

Landmarks in understanding the central nervous control of the cardiovascular system

Abstract: In this Paton Lecture I have tried to trace the key experiments that have developed ideas on how the brain regulates the cardiovascular system. It is a personal view and inevitably, owing to constraints on space and time, I have not been able to cover areas such as the nucleus tractus solitarius and cardiac vagal neurones, although I acknowledge that some may consider the story is incomplete without them. Starting with the crucial discovery of vasomotor nerves and 'vasomotor tone', the patterns of activity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
58
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 170 publications
(235 reference statements)
1
58
0
4
Order By: Relevance
“…Based on the available information regarding medullo-spinal cardiovascular regulatory areas (Coote, 2007;Gordon and Sved, 2002;Guyenet, 2006;Sapru, 2002Sapru, , 2004Talman et al, 1984), the following mechanism may be involved in mediating the cardiovascular responses elicited by MCH microinjections into the mNTS. MCH stimulates mNTS neurons as shown by direct pressure micro-applications of this peptide to these neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the available information regarding medullo-spinal cardiovascular regulatory areas (Coote, 2007;Gordon and Sved, 2002;Guyenet, 2006;Sapru, 2002Sapru, , 2004Talman et al, 1984), the following mechanism may be involved in mediating the cardiovascular responses elicited by MCH microinjections into the mNTS. MCH stimulates mNTS neurons as shown by direct pressure micro-applications of this peptide to these neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The nucleus tractus solitarius (NTS) is one of the medullary structures that plays an important role in the central regulation of cardiovascular function (for reviews see: Coote, 2007;Gordon and Sved, 2002;Guyenet, 2006;Sapru, 2002Sapru, , 2004Talman et al, 1984). The presence of MCH containing fibers and MCH-1 receptors has been demonstrated in the NTS (Hervieu et al, 2000;Zamir et al, 1986a,b).…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26][27] Importantly, it also receives the inputs from the paraventricular nucleus of the hypothalamus, which is known as a key nucleus of the central cardiovascular regulation. 22,28,29 Therefore, we focused on the RVLM in our studies. Other investigators have also confirmed our initial observations, and other details have been further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Key Words: cardiovascular control Ⅲ GABA Ⅲ substance P T he parvocellular subdivision of the hypothalamic paraventricular nucleus (PVN) contains both hypothalamicpituitary-adrenal axis control neurons, and spinally-projecting cardiovascular control neurons. [1][2][3][4][5][6] Estimates suggest that up to 2000 neurons project directly from the PVN to the intermediolateralis (IML) of the spinal cord. 7-9 These projecting parvocellular neurons have been implicated in a number of facets of cardiovascular control.…”
mentioning
confidence: 99%